FAKTOR YANG BERHUBUNGAN DENGAN EKSKRESI YODIUM DALAM URIN DI KABUPATEN GROBOGAN JAWA TENGAH - Widagdo, Dhuta; Kartono, Djoko; Nurcahyani, Yusi Dwi; Samsudin, M.; Ihsan, Nur (Media Penelitian dan Pengembangan Kesehatan, 2009)
Universal salt iodination (USI) is global policy for eliminating iodine deficiency disorder (IDD), and the content of iodine salt was 30-80 ppm. Survey 2003 show that 35% urine iodine excretion (UIE) of school children is was high, more than 300 µg/L, survey 2004 in Grobogan district in central Java by Department of Health show that UIE is was high to. The objective of the study is to conduct some factors that related with level of UIE in district of Grobogan, Central Java. Method: This study was comparative cross sectional study. Elementary school children were collected by random and divided into three areas, area I was elementary school children with UIE high level, area II was optimal UIE anda area III was UIE in adequate. Total sample for UIE level was 242 elementary school children, by spectrohptometer. Sample of salt was 242, measured by titration, and 76 samples of drinking water was collected by spectrophotometer. Goitogenic and iodine UIE optimal (area 11) and UIE adequate (area III). Total to sample is 242 school children, 242 sample of salt, 76 sample of drinking water. Goitrogenic and iodine intake were collected by FFQ and recall 24 hour. The data was analysis by univariat, bivariat and regressi multivariate. There are 24,1% adequate iodine in salt at area I, 2,6% at area II and 7,3% at area III. The mean of iodine content in water drinking in area I is 156.74 µg/L, area II is 189.06 µg/L, and area III is 84.03 µg/L. Median UEI in area I is 542 µg/L, area II is 502 µg/L and area III is 467 µg/L. There are significantly factors related to UEI is iodine content in water drinking.   Key words : Urine Iodine Excretion, Iodine Water Drinking, Iodine Salt